DeepSeek+ teaching design research and analysis - Liu Xiaoyan (ITM Web of Conferences)
This paper explores the concept, theoretical foundation, design principles, implementation strategies, and effectiveness evaluation of DeepSeek+ instructional design. Research shows that DeepSeek+ instructional design integrates advanced information technology and educational philosophies, providing teachers with new tools and methods to enhance teaching outcomes and student learning experiences. This design emphasizes personalized learning, data-driven instructional decisions, and interactivity, offering new perspectives for educational innovation. The research findings have significant theoretical and practical implications for advancing educational informatization and teaching reform.